GOVERNMENT COMMUNICATION AND INTERNET RESPONSES: PROFILE OF PRIME MINISTER KRIŠJĀNIS KARIŅŠ IN SELECTED DIGITAL MEDIA USERS’ COMMENTS DURING THE COVID-19 PANDEMIC (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Perceptions play a pivotal role in assessment of efficiency of government communication. Informed by the strategic narrative conceptual framework this study looks at perception of government communication in Internet comments during three essential dates in conquering the COVID-19 pandemic in Latvia: introduction of emergency situations on March 12 and November 6, 2020, and introduction of a curfew on December 29, 2020. The study uncovers how often and how the main spokesperson in government communication – the Prime Minister of Latvia Krišjānis Kariņš – is framed in comments of three online news media in Latvia (Apollo, Delfi, Tvnet) in Latvian and Russian. Using a digital tool for online comments analysis - the Index of Internet Aggressiveness (IIA), a data set is created of 244 comments, containing a key word “Kariņš” in various cases in Latvian and Russian. Qualitative content analysis is applied to extract and to compare the frequency of appearance and the framing of Kariņš over the course of the pandemic in Latvia. The findings reveal that Kariņš appears in comments significantly more after news in Latvian than in Russian, and has been commented five times more in Delfi than in Tvnet and Apollo together. The comments in Latvian are more aggressive than in Russian, and their emotional tone increases towards the end of 2020. In majority of comments the framing is negative involving attributes of irresponsibility, superficiality, indecisiveness and danger; yet positively framed rigidity and decisiveness of Kariņš can be observed too.IIA is an online comment analysis tool, incorporating a machine learning program, which analyses users’ comments on news on online news sites according to pre-selected keywords to grasp the commenters’ verbal aggressiveness. In March 2021 the IIA data set consists of ~25.08 million comments; ~ 616.62 million word usage in written commenting and ~ 1357.40 thousand news.